2006
DOI: 10.1016/j.elecom.2006.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer enhancement produced by laser induced cavitation

Abstract: A microelectrode is used to measure the mass transfer perturbation and characteristics during the growth and subsequent collapse of a single bubble (which following its initial expansion, achieved a maximum radius, R m , of ~ 500-1000 µm). This mass transfer enhancement was associated with the forced convection, driven by bubble motion, as the result of a single cavitation event generated by a laser pulse beneath a 25 µm diameter Au microelectrode. Evidence for bubble growth and rebound is gained from the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This jetting, together with acoustic streaming, is thought to lead to random punctuation and disruption of the mass-transfer boundary layer at the electrode surface at close electrode-to-horn separations. Birkin et al 21,22 also showed that the nature of the solvent is paramount in assigning limiting currents. For example, the violence of cavitational events is strongly dependent on solvent vapor pressure as well as the ultrasonic power.…”
mentioning
confidence: 99%
“…This jetting, together with acoustic streaming, is thought to lead to random punctuation and disruption of the mass-transfer boundary layer at the electrode surface at close electrode-to-horn separations. Birkin et al 21,22 also showed that the nature of the solvent is paramount in assigning limiting currents. For example, the violence of cavitational events is strongly dependent on solvent vapor pressure as well as the ultrasonic power.…”
mentioning
confidence: 99%
“…89,90 Studies were also undertaken on the bubble activity which leads to cleaning, such as bubble collapse and the formation of high-speed jets as bubbles involute during collapse. 91,92 This combined experience led to the development of cleaning apparatus which is currently under discussion for commercialization in a University of Southampton spin-out company.…”
Section: Ultrasonic Cleaningmentioning
confidence: 99%
“…5,6 Numerous techniques have been developed to create cavitation in a laboratory setting, including boiling, 7 syringe injection, spark generation, 8 focused ultrasound, 9 neutron sources, 10 and focused lasers. 11,12 Compared with other methods, focused laser nucleation is attractive because it offers excellent spatial and temporal control and does not require any intrusive parts to contact the cavitating medium. Focused laser nucleation generally works by optical dielectric breakdown of the medium [13][14][15] at the focal point but can also work by quickly depositing heat to impurities 15,16 or nanoparticles.…”
Section: Introductionmentioning
confidence: 99%